2022
DOI: 10.1093/jacamr/dlad001
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of time lag between antibiotic use and rise of resistant pathogens among hospitalized adults in Europe

Abstract: Background Antimicrobial resistance (AMR) causes substantial health and economic burden to individuals, healthcare systems and societies globally. Understanding the temporal relationship between antibiotic consumption and antibiotic resistance in hospitalized patients can better inform antibiotic stewardship activities and the time frame for their evaluation. Objectives This systematic review examined the temporal relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Data obtained across all pathogens (GNB or GPB) showed that the development of antibiotic resistance tends to occur over 0 to 6 months following exposure to antibiotics. 31 Therefore, the data agreed with the rapid changes in antibiotic resistance before and during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 69%
“…Data obtained across all pathogens (GNB or GPB) showed that the development of antibiotic resistance tends to occur over 0 to 6 months following exposure to antibiotics. 31 Therefore, the data agreed with the rapid changes in antibiotic resistance before and during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 69%
“…Eliminating the pressure from selected antibiotics such as FQ may not only favor a reduction in MRSA presence but also prompt a rapid decline in resistance. Previ-ous reviews [12,22,[45][46][47] have evaluated the temporal relationship between antibiotic consumption and resistance development in outpatient and primary care settings. Bell et al [12] included 243 studies (case-control, cross-sectional, ecological, and experimental studies) on all antibiotics and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews show the development of antibiotic resistance mainly occurs between 0 and 6 months after the use of related antibiotics. 37 Second, human factors and equipment contribute to the increase of MDR organisms. The use of Personal Protective Equipment (PPE), which was meant to protect healthcare staff and reduce infection, led to suboptimal utilization and disease transmission.…”
Section: Discussionmentioning
confidence: 99%